PLAYING WHILE LEARNING IN ELEMENTARY SCHOOL : APPLICATIONS OF THE MOVING TWIN GAME IN MATHEMATICS: Bermain Sambil Belajar di Sekolah Dasar : Penerapan Pembelajaran Moving Twin pada Pembelajaran Matematika - Vella Ayu Suci Maharani; Dzulfikar Akbar Romadhon (Journal for Technology and Science, 2024)
The competence that exists in an educator is dynamic which means that it also develops in accordance with advances in science and technology. Educators are required to always be creative as well as innovative in the learning activities they manage. Policies in Indonesia made by the government aim for educators to be able to increase the potential in themselves both in pedagogical competence, personality, social activities, and professional competence. The problem found in the field is that teachers do not have a deep understanding of the importance of learning models in teaching and learning activities in the classroom. Therefore, the learning atmosphere is often monotonous and students are not co-operative. Renewal in learning needs to be done so that learning objectives are achieved. This study aims to determine the effectiveness of learning while playing Moving Twin in mathematics. The research was conducted in one of the schools in Sidoarjo Regency. Data collection used observation, interview, and documentation techniques. So that the results obtained that the application of learning while playing is very effective in building understanding of the material by students. In addition, the increase in grades obtained was also achieved, students were able to work well together and the learning atmosphere became effective